2021
DOI: 10.1002/csc2.20627
|View full text |Cite
|
Sign up to set email alerts
|

Early sowing increases grain yield and cooking and eating quality of machine‐transplanted rice in eastern China

Abstract: In this study, field experiments were conducted in 2 yr with two rice varieties to compare use of light and temperature resources, crop growth characteristics, yield traits, and cooking and eating quality of machine-transplanted rice (Oryza sativa) in rice-wheat (Triticum aestivum) double cropping system among five sowing dates.The results showed that the total growth duration, total cumulative temperature, and total cumulative solar radiation and total biomass production from transplanting to maturity decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The results showed that delaying the sowing date shortened the vegetative growth period and the population of rice. The shortening of the booting stage decreased the number of spikelets and grains, and delaying the heading date decreased the daily average temperature and effective accumulated temperature at the filling stage, which led to lower grain filling [39,40]. In this study, it was greatly affected by low temperatures; the main component was temperature resources during the earlier stage and panicles, and the temperature was the main influencing factor at different sowing dates [41].…”
Section: Discussionmentioning
confidence: 90%
“…The results showed that delaying the sowing date shortened the vegetative growth period and the population of rice. The shortening of the booting stage decreased the number of spikelets and grains, and delaying the heading date decreased the daily average temperature and effective accumulated temperature at the filling stage, which led to lower grain filling [39,40]. In this study, it was greatly affected by low temperatures; the main component was temperature resources during the earlier stage and panicles, and the temperature was the main influencing factor at different sowing dates [41].…”
Section: Discussionmentioning
confidence: 90%
“…Increasing numbers of studies have shown that climate change has had a huge impact on the natural and ecological systems during the last century. The response of vegetation to climate warming is mainly studied by analyzing satellite data, such as changes in net primary productivity (Huang et al., 2020; Liu et al., 2019; Wen et al., 2018), normalized difference vegetation index (Jiao et al., 2021), vegetation greening (Lawal et al., 2019; Li et al., 2016; Zou et al., 2020), phenology (Su et al., 2020), biotic province (Correa‐Metrio et al., 2011; Lucht et al., 2006; Sun et al., 2017), net biocommunity productivity (Huang et al., 2019), pasture output (Habermann et al., 2019; Lu & Lu, 2002), forest fire (Murdiyarso & Adiningsih, 2006; Oris et al., 2014), and crop quality (Li et al., 2021; Rasel Parvej et al., 2020). Climate change is expected to reduce global wheat production by 1.9% by the middle of the century, with African and South Asian countries expected to have the worst impacts, average production cuts by 2050 are 15% and 16%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, timely transplanting of paddy seedlings helps to attain the optimal productivity [11]. Under field condition, the impact of temperature on phenological development and crop productivity can be examined by accumulated heat unit system since plants require a definite temperature before reaching the certain physiological stage [12].…”
Section: Introductionmentioning
confidence: 99%